Integrative transcriptome and WGCNA analysis reveal key genes mainly in response to Alternaria alternata in Populus simonii × P. nigra - Liu, Siyuan; Dai, Lijuan; Qu, Guanzheng; Lu, Xinming; Pan, Hong; Fu, Xiaoyu; Dong, Airong; Yang, Libin (Frontiers in Plant Science, 2025)
In order to explore the molecular mechanisms of Populus simonii × P. nigra response to stress and screen for genes conferring resistance to Alternaria alternata, we carried out measurements of physiological and biochemical indices and transcriptomic sequence analysis of leaves of Populus simonii × P. nigra inoculated with A. alternata. The results showed that the variation trends of multiple hormone contents and enzyme activities were broadly similar at different time points, with H2O2, SA, JA, PPO, SOD, PAL and POD showing a trend of increasing and then decrease after inoculation with the pathogen. The contents of H2O2 peaked on the second day and subsequently declined. The contents of SA and JA, as well as the enzymatic activities of SOD, PAL, and POD, reached their maxima on the third day before exhibiting a downward tendency. In contrast, the activity of PPO peaked on the fourth day. Whereas ABA content continued to increase until the fifth day and CAT content decreased and then increased. We subsequently identified 14,997 differentially expressed genes (DEGs) among the transcriptomic sequences(|log2FoldChange| > 1 and FDR value < 0.05), with genes encoding members of the ERF, MYB, bZIP, and WRKY transcription factor families being differentially expressed. Gene modules that were significantly associated with the ABA, PAL, JA, and SOD activity were identified using weighted gene co-expression network analysis (WGCNA). Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis showed that these genes were mainly related to biological stress, signal transduction, cell wall, and photosynthesis. Within these modules, we also identified hub genes in the regulatory network, including GLK1/2 transcriptional activators, 14-3-3 proteins, cytosine 5 methyltransferases, and a variety of proteins associated with photosynthesis and respiration. This study showed that these hub genes, which play a pivotal role in the co-expression network, which may indicate a potential role in defense process of Populus simonii × P. nigra against A. alternata. Additionally, we analyzed the gene expression regulation and defense mechanisms of Populus simonii × P. nigra adversity stress, providing new insights into how plants respond to biological stress.